Identification and molecular characterization of adenovirus types (HAdV‐8, HAdV‐37, HAdV‐4, HAdV‐3) in an epidemic of keratoconjunctivitis occurred in Pune, Maharashtra, Western India. Issue 12 (18th May 2016) - Gopalkrishna, Varanasi; Ganorkar, Nital N.; Patil, Pooja R.
Abstract : Epidemic keratoconjunctivitis (EKC) is a highly contagious infectious disease of the ocular surface and is caused mainly due to adenoviruses species D, B, and E. The present study was carried out to identify and characterize the viral etiological agents associated with the keratoconjunctivitis cases reported from Pune (Maharashtra), Western India between November–December 2013 and January, October–November 2014. Conjunctival swab specimens (n = 23) obtained from keratoconjunctivitis patients were subjected to detection of Adenovirus (AdV) and Enterovirus (EV) by PCR/RT‐PCR using hexon and 5′ NCR gene specific primers, respectively. Molecular typing of AdV and EV positive specimens was carried out by amplifying penton, fiber, and VP1 genes, respectively followed by sequencing and phylogenetic analysis. In this study, human adenovirus (HAdV) was identified as an etiological agent. None of the clinical specimens were found positive for enterovirus. AdV positivity in keratoconjunctivitis cases was found to be 60.9% (14/23). Fourteen of the HAdV positive strains, all of them were amplified by hexon gene, nine strains by fiber gene, and all 14 strains by penton gene specific primers. Sequencing of all HAdV positive samples revealed the presence of HAdV‐8, HAdV‐37, HAdV‐3, and HAdV‐4. All Indian strains showed highest nucleotide identity with the reference strains reported worldwide. The study revealed the circulation of HAdV‐8 (78.6%) as predominant AdV strain followed by HAdV‐37, HAdV‐3, and HAdV‐4 (7.2%) identified in the epidemic keratoconjunctivitis. Multiple types of AdVs in EKC reported for the first time in Western India. J. Med. Virol. 88:2100–2105, 2016 . © 2016 Wiley Periodicals, Inc.